Absence of Statistical and Scientific Ethos: The Common Denominator in Deficient Forensic Practices. Issue 1 (1st January 2017) - Tobin, William A.; Sheets, H. David; Spiegelman, Clifford
ABSTRACT: Comparative Bullet Lead Analysis (CBLA) was discredited as a forensic discipline largely due to the absence of cross-discipline input, primarily metallurgical and statistical, during development and forensic/judicial application of the practice. Of particular significance to the eventual demise of CBLA practice was ignorance of the role of statistics in assessing probative value of claimed bullet "matches" at both the production and retail distribution levels, leading to overstated testimonial claims by expert witnesses. Bitemark comparisons have come under substantial criticism in the last few years, both due to exonerations based on DNA evidence and to research efforts questioning the claimed uniqueness of bitemarks. The fields of fire and arson investigation and of firearm and toolmark comparison are similar to CBLA and bitemarks in the absence of effective statistical support for these practices. The features of the first two disciplines are examined in systemic detail to enhance understanding as to why they became discredited forensic practices, and to identify aspects of the second two disciplines that pose significant concern to critics.